Pelatihan smart packaging design sebagai upaya peningkatan branding dan nilai jual produk kuliner UMKM - Rapiyanta, Paulus Tofan; Andriani, Anik; Purnamawati, Annida; Safitri, Lina Ayu (Nur Science Institute, 2025)
The culinary MSME sector in Desa Prima Gayatri, Bangunjiwo, Kasihan, Bantul, Yogyakarta Special Region, faces challenges due to unappealing packaging designs, resulting in low consumer interest and limited product competitiveness. This issue arises from the lack of understanding and digital design skills among business owners in creating professional packaging. This community service program aims to train MSME owners to design their product packaging independently using free digital platforms. The smart packaging design approach was implemented to enhance packaging aesthetics, strengthen branding, and increase product value. The training was conducted systematically through several stages, including a needs assessment survey, module development, theoretical and practical training sessions, and evaluation through questionnaires and post-training monitoring. The evaluation results showed a significant improvement in participants' abilities. Based on data from 22 respondents, digital design skills increased by 81%, with an average score of 4.45 out of 5. Participant satisfaction with the training materials and methods was also high, with an average score of 4.59, and 95.45% of participants agreed that the training effectively addressed their challenges. Participants successfully created new packaging designs that were more attractive and professional, enhancing product image and consumer interest.